2020
DOI: 10.1080/19476337.2020.1805514
|View full text |Cite
|
Sign up to set email alerts
|

Application of heat-moisture-treated banana flour as composite material in hard biscuit

Abstract: Composite biscuits made of heat-moisture-treated banana flour and wheat flour with ratio ranging from 25 to 75% were characterized for its postprandial glucose response in mice, diffraction pattern by X-ray diffraction, organoleptic and texture properties. Biscuit made of 100% wheat flour was used as a control. Composite biscuits resulted in lower blood glucose response, lower glycemic index and load due to its resistant starch and slowly digestible starch content as well as lipid-starch complex. Composite bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…Most studies have focused on the fortification of pasta and its effects on the final quality. Moreover, studies that report the thermal modification of flours and starches, used for the preparation of various food products, are focused on determining the effect of the modification on the digestibility properties of food components, such as resistant starch, available starch and slow digesting starch (Gou et al ., 2019; Cahyana et al ., 2020; Zou et al ., 2020). Only a few studies relate the effect of thermally modified flours on product quality (Kaur et al ., 2016; Cahyana et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on the fortification of pasta and its effects on the final quality. Moreover, studies that report the thermal modification of flours and starches, used for the preparation of various food products, are focused on determining the effect of the modification on the digestibility properties of food components, such as resistant starch, available starch and slow digesting starch (Gou et al ., 2019; Cahyana et al ., 2020; Zou et al ., 2020). Only a few studies relate the effect of thermally modified flours on product quality (Kaur et al ., 2016; Cahyana et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The change in starch structure could alter the interaction of pectin with starch and consequently would change digestibility and functional properties. Study on HMT starch application in food product such as biscuit demonstrated an encouraging result in terms of postprandial glucose response (Cahyana et al, 2020). This result shows that HMT application in food product would be interesting.…”
Section: Introductionmentioning
confidence: 70%
“…These modifications have been reported to change not only physicochemical properties but also starch digestibility (Handarini et al, 2020b;Jiang et al, 2014;Marta, Cahyana, Arifin et al, 2019;Quintero-Castaño et al, 2020). In food products, non-starch components can interact with starch and affect digestibility and physicochemical properties of starch (Cahyana et al, 2020;Handarini et al, 2020a;Kim & BeMiller, 2012;G. Li & Zhu, 2017;Marta, Cahyana, Djali et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Lately, there has been a continuous and consistent ascent in shopper interest inwheat-free foods (Triticum aestivum) to lessen the danger of a problem known as celiac disease. Studies recommended that celiac disease can be treated by dodging the utilization of gluten (Cahyana et al, 2020). In 2007, the Food and Drug Administration (FDA) introduced a labeling requirement for gluten-free foods to fulfill the interest for high-quality gluten-free cookies/ bread with comparable quality with wheat flourdependent on cookies and bread.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 20% of banana creation isn't popularized because of size and appearance defects, raising their losses. Along these lines, green banana flour creation has been offered as an answer for high paces of waste among banana crops by the two analysts and authorities of different nations to provide a means of effectively utilizing fruits rejected as unsuitable for sale or export (Cahyana et al, 2020). According to Falcomer et al (2019), most people are familiar with yellow bananas and consume them regularly for their nutritional profile, but do not usually consume green and unripe bananas due to the typical hardness and their high astringency.…”
Section: Introductionmentioning
confidence: 99%